EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA FLIPBOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK KELAS I SEKOLAH DASAR - Gita Laurenza. S; Suci Perwita Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this study was to describe the effectiveness of the Problem based learning model assisted by flipbook media that can improve students' early reading skills. The method used in this study is Classroom Action Research (CAR). The data collection technique uses observation techniques with observation sheets and early reading test results. The subjects of this study were 25 students of class 1 A of SD Negeri 060858 Medan Tembung. Based on the results of the study, it shows that the process of implementing the problem based learning model assisted by flipbook media can improve the early reading skills of class 1 A students of SD Negeri 060858 Medan Tembung. The increase in early reading skills can be seen from the results of the early reading test carried out in 2 learning cycles. Before the application of the Problem based learning model assisted by flipbook media or pre-cycle, the classical completion results were 16%. In cycle I, classical completion was 40%, while in cycle II, classical completion was 84%.